0% found this document useful (0 votes)
36 views

Functions 2 Composite Functions

This document discusses composite functions, which are functions composed of other functions performed in sequence. It provides examples of calculating composite functions fg(x) and gf(x) using basic functions like f(x)=x^2 and g(x)=x-4. The key points are that composite functions allow combining multiple functions, the order of functions matters, and they can be used to model more complex relationships by breaking them into sequential steps.

Uploaded by

M J
Copyright
© © All Rights Reserved
Available Formats
Download as PPTX, PDF, TXT or read online on Scribd
0% found this document useful (0 votes)
36 views

Functions 2 Composite Functions

This document discusses composite functions, which are functions composed of other functions performed in sequence. It provides examples of calculating composite functions fg(x) and gf(x) using basic functions like f(x)=x^2 and g(x)=x-4. The key points are that composite functions allow combining multiple functions, the order of functions matters, and they can be used to model more complex relationships by breaking them into sequential steps.

Uploaded by

M J
Copyright
© © All Rights Reserved
Available Formats
Download as PPTX, PDF, TXT or read online on Scribd
You are on page 1/ 10

COMPOSITE FUNCTIONS

Starter
Answer these questions, based on the following functions:

𝑓 ( 𝑥 )=5 𝑥 +5 𝑔 ( 𝑥 )=9 𝑥 − 4 h ( 𝑥 ) =𝑥2 −3 𝑥 − 4


1) Find the value of 2) Find the value of x if: 3) Find the value of x if f(x) = 2g(x)
each function if x = 4 a) f(x) = 65
b) g(x) = -22
𝑓 ( 𝑥 )=5 𝑥 +5 Sub in 4
𝑓 ( 𝑥 )=2 𝑔(𝑥) Replace f(x)
𝑓 ( 4 )=5 (4 )+5 Calculate
𝑓 ( 𝑥 )=5 𝑥 +5 Replace f(x) 5 𝑥+5¿ 2(9 𝑥 − 4)
and g(x)
Expand
𝑓 ( 4 )=25 65=5 𝑥+5 Subtract 5 bracket
5 𝑥+5¿ 18 𝑥 −8 Add 8,
60=5 𝑥 Divide by 5
𝑔 ( 𝑥 )=9 𝑥 − 4 Sub in 4 12=𝑥 13=13 𝑥 Subtract 5x
Divide by 13
𝑔 ( 4 )=9 (4)− 4 Calculate 1=𝑥
𝑔 ( 4 )=32 𝑔 ( 𝑥 )=9 𝑥 − 4 Replace g(x)
−22=9 𝑥 − 4 Add 4
h ( 𝑥 ) =𝑥2 −3 𝑥 − 4 Sub in 4 −18=9 𝑥 Divide by 9
h ( 4 ) =( 4)2 −3 ( 4 ) − 4
Calculate −2=𝑥
h ( 4 ) =0
Composite Functions
• Today we will be continuing our work on
functions

• We will be looking at problems involving


‘Composite functions’

• A Composite Function is one which is made


up of several functions performed in a
certain order
Composite Functions
Lets start with the following functions:

𝑓 ( 𝑥 )=𝑥 2 𝑔 ( 𝑥 )=𝑥 − 4

1a) Calculate fg(8) The function fg(8) means you calculate g(8),
and then calculate f(the answer)
𝑔 ( 𝑥 )=𝑥 − 4
Sub in 8
 So substitute 8 into g(x) to find the
𝑔 ( 8 )=8 − 4 value of g(8)
Calculate
𝑔 ( 8 )=4  Then take the answer, and substitute it
into f(x)
𝑓 ( 𝑥 )=𝑥 2
Sub in 4, which was g(8)
𝑓𝑔 ( 8 ) =( 4)2 We are calculating ‘f of g of 8’
Calculate
𝑓 𝑔 ( 8 )=16

Therefore: 𝑓𝑔(8)=16
Composite Functions
Lets start with the following functions:

𝑓 ( 𝑥 )=𝑥 2 𝑔 ( 𝑥 )=𝑥 − 4

1b) Calculate gf(8) The function gf(8) means you calculate f(8),
and then calculate g(the answer)
𝑓 ( 𝑥 )=𝑥 2
Sub in 8
 So substitute 8 into f(x) to find the
𝑓 ( 8 ) =(8)2
Calculate value of f(8)
𝑓 ( 8 ) =64  Then take the answer, and substitute it
into g(x)
𝑔 ( 𝑥 )=𝑥 − 4
Sub in 64, which was f(8)
𝑔 𝑓 ( 8 )=64 − 4 We are calculating ‘g of f of 8’
Calculate
𝑔 𝑓 ( 8 )=60 Notice that the order is
important – you get a different
Therefore: 𝑔𝑓 (8)=60 answer if it is changed!
Composite Functions
Lets start with the following functions:

𝑓 ( 𝑥 )=𝑥 2 𝑔 ( 𝑥 )=𝑥 − 4

1c) Calculate fg(x) The function fg(x) means you calculate g(x),
and then calculate f(the answer)
𝑔 ( 𝑥 )=𝑥 − 4 Sub in x (actually,
 So substitute x into g(x) to find the
𝑔 ( 𝑥 )=𝑥 − 4 nothing happens!)
value of g(x)
 Then take the answer, and substitute it
𝑓 ( 𝑥 )=𝑥 2 into f(x)
Sub in (x – 4) for all ‘x’
2 terms (This was g(x))
𝑓 ( 𝑥 − 4 ) =(𝑥 − 4)
Calculate We are calculating ‘f of g of x’
2
𝑓 ( 𝑥 − 4 ) =𝑥 −8 𝑥+16

Therefore: 𝑓𝑔(𝑥)=(𝑥 − 4)2


Composite Functions
Lets start with the following functions:

𝑓 ( 𝑥 )=3 𝑥 −1 𝑔 ( 𝑥 )=𝑥 2+1 What this does is give us a


single function that can replace
the functions f and g (in this
particular order)
2a) Calculate fg(x)
 3x2 + 2
𝑔 ( 𝑥 )=𝑥 2+1
Replace g(x) with its expression in fg(x) This function is equivalent to
𝑓𝑔 ( 𝑥 )¿ 𝑓 ( 𝑥2 +1) performing x2 + 1 followed by
3x - 1

𝑓 ( 𝑥 )=3 𝑥 −1 So we need to find f(x2 + 1)


 Replace all ‘x’ terms with ‘x2 + 1’ terms
𝑓 ( 𝑥 2 +1 )=3( 𝑥 2+1)− 1
Expand bracket
𝑓 ( 𝑥 +1 )=3 𝑥 +3 −1
2 2

Simplify
𝑓 ( 𝑥 +1 )=3 𝑥 +2
2 2
Composite Functions
Lets start with the following functions:

𝑓 ( 𝑥 )=3 𝑥 −1 𝑔 ( 𝑥 )=𝑥 2+1 What this does is give us a


single function that can replace
the functions f and g (in this
particular order)
2a) Calculate gf(x)
 9x2 - 6x + 2
𝑓 ( 𝑥 )=3 𝑥 −1
Replace g(x) with its expression in fg(x) This function is equivalent to
𝑔𝑓 ( 𝑥 )¿ 𝑔(3 𝑥 −1) performing 3x – 1 followed by
x2 + 1

𝑔 ( 𝑥 )=𝑥 2+1 So we need to find g(3x - 1)


2  Replace all ‘x’ terms with ‘3x - 1’ terms
𝑔 ( 3 𝑥 − 1 )=( 3 𝑥 − 1 ) +1
Expand bracket
2
𝑔 ( 3 𝑥 − 1 )=9 𝑥 − 6 𝑥+1+1
Simplify
2
𝑔 ( 3 𝑥 − 1 )=9 𝑥 − 6 𝑥+2
Plenary
𝑓 ( 𝑥 )=𝑥 2 +8 𝑔 ( 𝑥 )=𝑥+ 4
Set equal to
Find the value of for which fg(x) = gf(x)
each other
𝑓𝑔 ( 𝑥 ) Find fg(x) 𝑔𝑓 ( 𝑥 ) Find gf(x) 𝑓𝑔 ( 𝑥 ) =𝑔𝑓 (𝑥)
¿ 𝑓 (𝑥+ 4) ¿ 𝑔 (𝑥 2 +8) 𝑥2 +8 𝑥+24=¿𝑥2 +12
𝑓 ( 𝑥 )=𝑥 2 +8 𝑔 ( 𝑥 )=𝑥+ 4 8 𝑥+24 =¿12
2
𝑓 ( 𝑥 +4 )= ( 𝑥 +4 ) +8 𝑔 ( 𝑥 + 8 ) =( 𝑥 + 8)+ 4
2 2 8 𝑥=−12
𝑓 ( 𝑥 +4 )=𝑥 2 +8 𝑥+16 +8 𝑔 ( 𝑥 2+ 8 ) =𝑥2 +12 𝑥=−1.5
𝑓 ( 𝑥 +4 )=𝑥 2 +8 𝑥+24
𝑔𝑓 ( 𝑥 )=𝑥 2+12
𝑓𝑔 ( 𝑥 ) =𝑥 2 +8 𝑥+24
Summary
• We have looked at composite functions

• We have seen how they can combine multiple functions into a


single one

• Sometimes the combined equation is simpler, and sometimes it


can be more complicated

• Composite functions can be used in games to describe motion


 The two separate functions could be based on horizontal
and vertical movement (eg – throwing a ball)
 You can choose these and then combine them to form an
equation for the exact location of a ball at a particular time…

You might also like